Persepsi Petani terhadap Penetapan Subak Anggabaya Sebagai Subak Lestari di Kota Denpasar - PRAMESTI, I GUSTI AYU WINDI; SUAMBA, I KETUT (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2020)
Farmer’s Perceptions of the Establishment of Subak Anggabaya as Subak Lestari in Denpasar City  Subak Lestari is an area developed in the city of Denpasar as a leading sector of the Denpasar Agriculture Office. One of the subaks developed is Subak Anggabaya, which makes efforts and action plans in preserving subaks. The establishment of sustainable subak in the city of Denpasar is made possible due to supervision and guidance provided, because it can support the increase in rice productivity for farmers. The purpose of this study was to determine the perceptions and expectations of farmers after the establishment of Subak Anggabaya as a sustainable subak in the city of Denpasar. The sampling was 41 respondents using simple random sampling method. Data analysis used descriptive qualitative by using a Likert Scale.The results showed that the perceptions of Subak Anggabaya farmers regarding the establishment of sustainable subak belonged to high category (80,31%). This was supported by the results achieved, shown by three aspects, namely the technical aspects which were also of high category (78,78%), the socio-cultural aspects belonged to high category as well (83,25%), and so were the economic aspects (78,90%). The conclusion of this study is that the perception of Subak Anggabaya farmers as sustainable subak in Denpasar City was very good. Suggestions that can be made for the government as the leading sector of the Department of Agriculture in the City of Denpasar is that it should socialize the sustainable subak programs intensively, and should guarantee the risk of crop failure for farmers.